2012
DOI: 10.1089/ars.2011.4105
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamics and Parkinson's Disease: Focus on Parkin

Abstract: Significance: Parkinson's disease (PD) is a prevalent neurodegenerative disease affecting millions of individuals worldwide. Despite intensive efforts devoted to drug discovery, the disease remains incurable. To provide more effective medical therapy for PD, better understanding of the underlying causes of the disease is clearly necessary. Recent Advances: A broad range of studies conducted over the past few decades have collectively implicated aberrant mitochondrial homeostasis as a key contributor to the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 117 publications
2
46
0
2
Order By: Relevance
“…In fact, the inhibition of the Aβ-ABAD interaction has been shown to reduce Aβ accumulation and to improve mitochondrial function in transgenic mice and neuroblastoma cells (Lim et al, 2011;Yao et al, 2011). ABAD converts estrone to estradiol, a key antioxidant compound for neurone survival whose intracellular levels are decreased due to the interaction between Aβ and ABAD, a phenomenon that may contribute to Aβ-induced toxicity (Yang et al 2007;Lim et al, 2011). In addition, ABAD is a component of the mitochondrial RNAse P involved in the processing of immature mitochondrial tRNAs (Holzmann et al, 2008).…”
Section: In Alzheimer´s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the inhibition of the Aβ-ABAD interaction has been shown to reduce Aβ accumulation and to improve mitochondrial function in transgenic mice and neuroblastoma cells (Lim et al, 2011;Yao et al, 2011). ABAD converts estrone to estradiol, a key antioxidant compound for neurone survival whose intracellular levels are decreased due to the interaction between Aβ and ABAD, a phenomenon that may contribute to Aβ-induced toxicity (Yang et al 2007;Lim et al, 2011). In addition, ABAD is a component of the mitochondrial RNAse P involved in the processing of immature mitochondrial tRNAs (Holzmann et al, 2008).…”
Section: In Alzheimer´s Diseasementioning
confidence: 99%
“…Finally, the high-temperature requirement A2 protein (HTRA2) is the last player in the field of PD. Mutations in this gene may increase the risk of PD, and increased ROS levels and altered mitochondrial morphology have been described in several cellular models of HTRA2 dysfunction (for a review see Lim et al, 2011). In addition, it seems to be an inductor of autophagy , but the precise role of this protein in PD, mitochondrial dynamics and autophagy is still unclear.…”
Section: Linking Oxidative Stress and Mitochondrial Dynamics In Pd Amentioning
confidence: 99%
“…Recent studies have revealed that two genes, whose mutations are linked to familial parkinsonism, i.e. parkin (encoding a ubiquitin ligase) and PINK1 (encoding a serine/ threonine kinase), are important for mitophagy (1). According to the proposed model (2), a key initial event that occurs upon mitochondrial depolarization is the selective accumulation of PINK1 on the outer membrane of the damaged organelle.…”
mentioning
confidence: 99%
“…The action of the PARKIN-PINK1 complex is to regulate mitochondrial morphogenesis and remove damaged mitochondria through a form of ALS (50,51). Mutations in PINK1 are associated with mitochondrial dysmorphogenesis and dysfunction, which are also characteristics of Parkinson's disease (52,53). In diabetic embryopathy, the aggregation of Parkin may perturb mitochondrial dynamics and protein quality control, thereby leading to embryonic malformations (15).…”
Section: Discussionmentioning
confidence: 99%